One-Year Outcome of Multiple Blood–Brain Barrier Disruptions With Temozolomide for the Treatment of Glioblastoma - Park, So Hee; Kim, Myung Ji; Jung, Hyun Ho; Chang, Won Seok; Choi, Hyun Seok; Rachmilevitch, Itay; Zadicario, Eyal; Chang, Jin Woo (Frontiers in Oncology, 2020)
Introduction : To overcome the blood-brain barrier (BBB) which interferes with the effect of chemotherapeutic agents, we performed multiple disruption of BBB (BBBD) with magnetic resonance-guided focused ultrasound (MRgFUS) on patients with glioblastoma (GBM) during standard adjuvant temozolomide (TMZ) chemotherapy. We report a one-year follow-up result of BBBD with TMZ for GBM. Methods: From September 2018 to January 2019, six patients were enrolled (4 men and 2 women, mean age: 55.83±11.03 years). Of the six patients, five underwent a total of 6 cycles of BBBD during standard TMZ adjuvant therapy. One patient underwent 3 cycles of BBBD but continued with TMZ chemotherapy. The one-year follow-up results of these 6 patients were reviewed. Results: The mean follow-up duration was 15.17±1.72 months. Two patients showed recurrence of tumor at 11 months and 16 months, respectively. One underwent surgery, and the other patient was restarted with TMZ chemotherapy due to the tumor location with highly possibility of surgical complications. The survival rate up to 1 year was 100% and the other four patients are on observation without recurrence. None of the six patients had immediate or delayed BBBD-related complications. Conclusion: Multiple BBBDs can be regarded as a safe procedure without long-term complication and it seems to have some survival benefits. However, since TMZ partially crosses the BBB, further extended study with large numbers would be needed to evaluate the benefits of BBBD resulting in an increase of TMZ concentration. This study opened a new therapeutic strategy for GBM by combining BBBD with a therapeutic agent which could not be used due to BBB.